Experimental Study on the Deactivating Effect of KNO3, KCl, and K2SO4 on Nanosized Ceria/Titania SCR Catalyst. (26th October 2015) - Chen, Xiongbo; Fang, Ping; Zeng, Wenhao; Liu, Kunyuan; Tang, Zhixiong; Cen, Chaoping
Abstract : Nanosized Ce/TiO2 is effective in selective catalytic reduction of NO with NH3 . The NO conversion of Ce/TiO2 is 93% at 370°C. However, addition of potassium using KNO3, KCl, or K2 SO4 as precursors effectively deactivates Ce/TiO2 . NO conversion at 370°C is reduced to 45%, 24%, and 16% after addition of KNO3, KCl, and K2 SO4, respectively, with a controlled K/Ce molar ration at 0.25. The deactivation may be attributed to the changes in the structural and chemical state of ceria and the degradation of surface acidity. The transformation of amorphous ceria into ceria crystals after potassium addition, together with the decrease of surface defects, is also determined. Oxygen diffusion in the process of ceria reduction is slow, and the redox cycle is slowed down. Moreover, the surface acid sites are markedly destroyed, leading to the reduced capacity of ammonia adsorption. These results may provide useful information for the application and life management of CeO2 /TiO2 in potassium-rich environments such as biofuel-fired boilers.